2018
DOI: 10.3892/ijo.2018.4593
|View full text |Cite
|
Sign up to set email alerts
|

miR-874 regulates multiple-drug resistance in gastric cancer by targeting ATG16L1

Abstract: Chemotherapy is an important treatment option for gastric cancer (GC); however, chemotherapy usually fails due to drug resistance, particularly multidrug resistance (MDR). In our previous studies, microRNA (miR)-874 was demonstrated to serve an important role in tumour growth, apoptosis and angiogenesis. In the present study, the precise roles and underlying mechanisms of miR-874 in MDR were investigated in GC. The overexpression of miR-874 reversed cancer cell drug resistance in vitro. According to reporter g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…In addition to ATG5, the inhibitory effects of miR-142-3p on therapeutic resistance can be mediated by targeting ATG16L1 [97]. Moreover, a recent study also indicated that autophagy inhibition in miR-874-3p over-expressing cells abrogates therapeutic resistance [104] (Table 3).…”
Section: Mirnas Regulating the Lipidation Of Lc3mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to ATG5, the inhibitory effects of miR-142-3p on therapeutic resistance can be mediated by targeting ATG16L1 [97]. Moreover, a recent study also indicated that autophagy inhibition in miR-874-3p over-expressing cells abrogates therapeutic resistance [104] (Table 3).…”
Section: Mirnas Regulating the Lipidation Of Lc3mentioning
confidence: 99%
“…Since both miR-129-3p and miR-129-5p (see Table 1) are derived from the same precursor, and both mature miRNA strands are functionally different in cells, it is feasible that over-expression of the miR-129 precursor in cancer cells using vector systems triggers cytoprotective autophagy, but inhibits ABCB1 levels. miR-410-3p HMGB1 Pancreatic cancer Over-expression of miR-410-3p improves gemcitabine-induced cell death and growth inhibition in drug-resistant cells [102] miR-520-3p ATG7 Hepatocellular carcinoma Replacement of miR-520-3p increases the sensitivity of drug-resistant cells to doxorubicin by enhancing cell death and growth inhibition [103] miR-874-3p ATG16L1 Gastric cancer Restoration of miR-874-3p sensitizes cells to 5-fluorouracil and cisplatin [104] Another recent study showed that RAB12 member RAS oncogene family (RAB12) is an endogenous mTORC1 inhibitory factor and protects cancer cells from drug-induced cell death by activating cytoprotective autophagy. RAB12 is targeted by miR-148-3p; therefore, the introduction of miR-148-3p in cancer cells can reverse therapeutic resistance [89] (Table 3).…”
Section: Mirnas Regulating Mtor and Mtorc1mentioning
confidence: 99%
“…Similarly, tumor suppressor miR-362-5p, miR-198, miR-574-3p, miR-876-3p, miR-874 and let-7b have been reported to reverse DDP resistance of gastric cancer cells via silencing suppressor of zeste 12 protein (SUZ12), fibroblast growth factor receptor 1 (FGFR1), zinc finger E-box binding homeobox transcription factor 1 (ZEB1), TMED3, autophagy-related 16-like 1 (ATG16 L1) and AURKB, respectively [117][118][119][120][121][122]. In addition, via targeting excision repair cross-complementing (ERCC), exogenous over-expression of tumor suppressor miR-122, miR-138-5p and miR-192-5p could also reverse DDP resistance of gastric cancer [48,123,124].…”
Section: Mirnas and Resistance To Platinum Drugsmentioning
confidence: 99%
“…Moreover, the lentiviral delivery of miR-495-3p efficiently decreases the growth of vincristine-resistant cells in vivo [ 318 ]. In addition, miR-874 inhibits autophagy via targeting ATG16L1, a positive regulator of autophagosome formation [ 322 ]. Both miR-874 overexpression and ATG16L1 knockdown elevate the efficacy of vincristine in gastric cancer cells [ 322 ] ( Figure 5 and Table 6 ).…”
Section: Mirnas Regulating the Sensitivity Of Cancer Cells To Phytmentioning
confidence: 99%
“…In addition, miR-874 inhibits autophagy via targeting ATG16L1, a positive regulator of autophagosome formation [ 322 ]. Both miR-874 overexpression and ATG16L1 knockdown elevate the efficacy of vincristine in gastric cancer cells [ 322 ] ( Figure 5 and Table 6 ).…”
Section: Mirnas Regulating the Sensitivity Of Cancer Cells To Phytmentioning
confidence: 99%